2013
DOI: 10.1210/jc.2012-3042
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Other Important Diabetes-Related Outcomes With Insulin vs Other Antihyperglycemic Therapies in Type 2 Diabetes

Abstract: Context:The safety of insulin in the treatment of type 2 diabetes mellitus (T2DM) has recently undergone scrutiny.Objective:The objective of the study was to characterize the risk of adverse events associated with glucose-lowering therapies in people with T2DM.Design and Setting:This was a retrospective cohort study using data from the UK General Practice Research Database, 2000–2010.Patients:Patients comprised 84 622 primary care patients with T2DM treated with one of five glucose-lowering regimens: metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
151
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(171 citation statements)
references
References 32 publications
8
151
1
11
Order By: Relevance
“…21 However, insulin therapy in people with T2DM also carries some risks, not least hypoglycaemia, as well as weight gain, which is often seen as a major disadvantage by patients. 20 A recent retrospective cohort study 22 controversially reported that the use of insulin therapy in T2DM was associated with an increased mortality rate in comparison with patients who were just on oral hypoglycaemic agents. However, this was not a randomised controlled trial and was likely to have been influenced by the fact that patients with poorer blood glucose control are treated with insulin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, insulin therapy in people with T2DM also carries some risks, not least hypoglycaemia, as well as weight gain, which is often seen as a major disadvantage by patients. 20 A recent retrospective cohort study 22 controversially reported that the use of insulin therapy in T2DM was associated with an increased mortality rate in comparison with patients who were just on oral hypoglycaemic agents. However, this was not a randomised controlled trial and was likely to have been influenced by the fact that patients with poorer blood glucose control are treated with insulin.…”
mentioning
confidence: 99%
“…22 However, the correct point at which to commence insulin therapy in T2DM and where it stands in relation to newer hypoglycaemic therapies such as glucagon-like peptide-1 (GLP-1) agonists and sodiumglucose co-transporter 2 (SGLT2) inhibitors, such as canagliflozin, has been controversial. 22 The most recent NICE guideline for management of T2DM in adults, published in December 2015, recommends initiating insulin either at the point of failure of two oral agents (HbA1c >58mmol/mol) or alternatively adding a third oral agent instead of insulin. 23 Insulin therapy combined with a GLP-1 agonist is recommended to be used only on the advice of diabetes specialists.…”
mentioning
confidence: 99%
“…Although several observational studies have investigated the association between sulfonylureas and cancer incidence or cancer-related mortality (3)(4)(5)(6)(7)(8)(9)(10)(11)16,17,22,23), only five focused on glyburide and cancer-related outcomes (2,6,13,16,17). Overall, these studies produced conflicting findings, with three reporting increased risks ranging from 150 to 250% (2,6,13) and two reporting decreased risks ranging from 20 to 50% (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, thiazolidinedione glucose lowering medicines are linked to heart failure and other cardiovascular mortality [8]. Insulin and sulphonylureas are linked to adverse outcomes in older people with diabetes and mortality [9,10]. Currie et al [9] described mortality hazard between 10 and 34% for these medicines in combination with metformin and even higher levels when they were used as monotherapy.…”
Section: Diabetes: a Significant Issue Also In Palliative Care Settingmentioning
confidence: 99%
“…Insulin and sulphonylureas are linked to adverse outcomes in older people with diabetes and mortality [9,10]. Currie et al [9] described mortality hazard between 10 and 34% for these medicines in combination with metformin and even higher levels when they were used as monotherapy. Glycaemic control is important with good control, HbA1c, <7% (53 mmol/mol) conferring benefits.…”
Section: Diabetes: a Significant Issue Also In Palliative Care Settingmentioning
confidence: 99%